Maxillary sinus bone augmentation and injectable plateletrich fibrin (I-PRF) for dental implant: a systematic review - Leonel, Mariana Messias (2025)
Introduction: In the context of bone regeneration for dental implants, maxillary sinus augmentation is a well-documented surgical technique and is one of the therapeutic options for implant placement in the atrophic posterior maxilla, particularly when the residual bone height is less than 5 mm. Several surgical techniques can be used to reconstruct the atrophic alveolar ridge, techniques alone or associated with autogenous, allogeneic, xenogenous grafts, and alloplastic biomaterials. Objective: It was carried out a systematic review to present the main scientific documentation on maxillary sinus augmentation and bone regeneration for dental implants. Methods: The PRISMA Platform systematic review rules were followed. The search was carried out from November 2024 to January 2025 in the Scopus, PubMed, Science Direct, Scielo, and Google Scholar databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Experimental and clinical studies (retrospective, prospective and randomized) with qualitative and/or quantitative analysis were included. Results and Conclusion: A total of 123 articles were found, and 35 articles were evaluated in full and 26 were included and developed in the present systematic review study. Considering the Cochrane tool for risk of bias, the overall assessment resulted in 25 studies with a high risk of bias and 31 studies that did not meet GRADE and AMSTAR-2. According to the GRADE instrument, most studies presented homogeneity in their results, with X2=90.8%>50%. It was concluded that the use of small and large bovine xenograft particles for maxillary sinus augmentation provides comparable bone formation, ensuring stable graft dimensions combined with high implant success and healthy peri-implant conditions. However, the small particle size resulted in better bone-graft contact, providing greater osteoconductivity than with the larger particle size. Based on the literary findings, it was shown that the fibrin-rich plasma is favorable for bone formation processes for dental implants, especially when combined with xenografts.